Herpes zoster in a patient with history of breast cancer: A case report - Pristia Widya Monica; Fitri Kasmitasari; Prasetyadi Mawardi (Universitas Aisyah Pringsewu, 2022)
Herpes zoster (HZ) is a disease caused by the reactivation of the varicella-zoster virus (VZV). Immunodeficiency, such as malignancy, is one of the causative factors of HZ. Clinically HZ manifests as erythematous macules within 12-24 hours, then develops into unilateral clustered vesicles that usually do not cross the body's midline and are confined to areas of the skin innervated by a sensory ganglion. Tzank test is a standard diagnostic tool for diagnosing HZ, as it can detect multinucleated giant cells. A 57-year-old woman presented to the outpatient dermatology and venereology clinic of Dr Moewardi General Hospital, painful, easily ruptured vesicles on her left chest spreading to her back, left armpit and arm. She was diagnosed with breast cancer five years ago. She had completed her cancer therapy, and in November 2020, she had a total mastectomy of her right breast. Physical examination obtained multiple unilaterally clustered vesicles, which were partially crushed on an erythematous base with some erosive areas in a C6 and T4 dermatomal distribution on the left side. Tzank examination showed multinucleated giant cells. She was treated with aciclovir tablets 800 mg/4.5 hours for ten days, gabapentin tablets 300 mg/24 hours for three days and then every 12 hours from day 4 to day 7, Neurosanbe® tablets/8 hours, wound care with 0.9% NaCl compression for 10 minutes every morning and evening, and mupirocin ointment 2% applied on the erosive area as well as salicyl talc on the unburst vesicles. Immunosuppressive conditions such as malignancies result in reduced cell-mediated immunity (CMI), which increases the risk of viral infections such as herpes zoster. Commonly people with malignancies have low CD4+ and CD8+ cell counts and reduced lymphocyte proliferation. All the above conditions can be risk factors for the development of HZ.Abstrak: Herpes zoster (HZ) adalah penyakit yang disebabkan oleh reaktivasi virus varicella zoster (VZV). Imunodefisiensi seperti keganasan, merupakan salah satu faktor penyebab HZ. Secara klinis, HZ bermanifestasi sebagai makula eritematosa dalam 12-24 jam dan kemudian berkembang menjadi vesikel berkelompok unilateral yang biasanya tidak melewati garis tengah tubuh dan terbatas pada area kulit yang dipersarafi oleh ganglion sensorik. Pemeriksaan Tzank merupakan alat diagnostik standar untuk mendiagnosis HZ karena dapat ditemukan multinucleated giant cells. Seorang wanita 57 tahun datang ke bagian dermatologi dan venereologi RSU Dr Moewardi dengan keluhan nyeri, lepuh mudah pecah pada dada kiri, meluas ke punggung, ketiak kiri dan lengan. Pasien didiagnosis menderita kanker payudara lima tahun yang lalu. Dia telah menyelesaikan pengobatan kanker dan menjalani mastektomi total payudara kanan pada November 2020. Pemeriksaan fisik didapatkan beberapa vesikel yang berkelompok unilateral dengan dasar eritem sebagian pecah membentuk krusta setinggi dermatom servikal 6 sampai dengan thorakal 4 (C6-T4) sinistra. Pemeriksaan Tzank menunjukkan multinucleated giant cells. Tatalaksana pada pasien dengan asiklovir tablet 800 mg/4,5 jam selama 10 hari, gabapentin tablet 300 mg/24 jam selama 3 hari dilanjutkan tiap 12 jam pada hari ke 4 sampai dengan hari ke 7, Neurosanbe® tablet/8 jam, rawat luka dengan kompres 0,9% NaCl selama 10 menit pada pagi dan sore hari, mupirosin salep 2% pada area erosi dan pada vesikel yang belum pecah diberikan bedak salisil. Kondisi imunosupresi seperti keganasan menyebabkan penurunan cell mediated immunity (CMI) yang meningkatkan risiko infeksi virus, seperti zoster. Secara umum, orang yang menderita keganasan memiliki sel CD4 + dan CD8 + yang rendah dan gangguan proliferasi limfosit. Semua kondisi di atas dapat menjadi faktor risiko munculnya HZ.